Neoplastic melanocytic pleural effusion in a Portuguese water dog. (7th December 2020) - Corda, Erica; Vilar Saavedra, Paulo; Berghoff, Nora; Smedley, Rebecca C.; Thomas, Jennifer S.
Abstract: A 9‐year‐old castrated male Portuguese water dog was presented following incomplete excision of a malignant melanoma at the left lip commissure by the referring veterinarian. Physical examination was otherwise unremarkable. The patient was staged using thoracic radiographs, abdominal ultrasound, and fine‐needle aspirates of the mandibular lymph nodes and spleen. Given the absence of any definitive evidence of metastasis, the malignant melanoma was surgically completely removed. The dog then received four melanoma vaccine doses as an adjuvant therapy and remained clinically healthy for more than 3 months after the last immunization. However, 232 days after the initial discovery of the lip mass, the dog was euthanized due to deterioration and a poor prognosis based on the presence of lung metastases and neoplastic melanocytic pleural effusion. The latter has been rarely reported in dogs, despite the high prevalence of oral malignant melanomas and the tendency of these tumors to metastasize to the lungs.